Rancangan Strategis Pemantapan Literasi Membaca Di Sekolah Di Era Digital - Anita Candra Dewi (Jurnal Pendidikan dan Pembelajaran, 2024)
Literacy is the ability to read and write that a person has. Literacy plays an important role in student character building. Character is something that is inherent in every individual and is not formed from birth, but rather influenced by various factors such as in the school, family and community environment. This article aims to explore the role of literacy culture in shaping students' character. Reading literacy is a very important basic skill for primary school students as it serves as a foundation for learning at the next level of education. This article aims to identify and explain effective strategies in improving reading skills and fostering interest in reading among students. Various methods such as the phonetic approach, shared reading and story-based learning are discussed as practical solutions to be implemented in the classroom. Through the implementation of effective literacy strategies, it is hoped that schools can create a learning environment that supports reading skills and encourages the formation of reading habits from an early age.